Big five personality traits and income - Rejthar, Jan; Frömmel, Tomáš; Brožová, Dagmar, 1958-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This bachelor thesis aims at inspection of the hypothesis: “Personality effects income.”An OLS regression model is used to analyze the hypothesis. The Big Five personality traitsmodel is employed as the taxonomy of personality and translated version of the IPIP 50questionnaire is utilized for assessment of personality of individuals, showing high level ofreliability. Results of the regression analysis are in favor of the hypothesis, becauseagreeableness shows negative and statistically significant effect. Secondary analysis of thedataset of the thesis show differences in personality between sexes in the cases of agreeablenessand neuroticism, both benefiting women, while analysis of the dataset fromopenpsychometrics.org shows differences in all five dimensions. Analysis of the influence ofpersonality on education is inconclusive.
Vedoucí práce: Tomáš Frömmel
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses